PENINGKATAN PRODUKTIVITAS PRODUKSI PALET KAYU DENGAN PENDEKATAN SIKLUS PDCA DAN KAIZEN 5S DI CV ARSITA JAYA - Mawabagja, Dico; An Khofiyah, Nida; Suhendra (Industry Xplore, 2025)
CV Arsita Jaya is a company engaged in the production of wooden pallets playing a crucial role in the supply chain of various industries, including manufacturing, logistics, and export. Wooden pallets are used as a base for storage and transportation of goods to ensure stability and facilitate loading and unloading processes. Therefore, effectiveness and efficiency in wooden pallet production are essential factors in supporting smooth distribution. However, the company faces challenges in workplace management such as disorganized production areas, inefficient layout, and long tool search times which directly impact employee productivity and production capacity. To address these challenges, this study implements the PDCA cycle approach and the Kaizen 5S method to improve workplace organization and efficiency. The results indicate that the implementation of these methods successfully reduced tool search time by 39.24% and improved the 5S evaluation score from inadequate to highly satisfactory. Additionally, the socialization of the 5S method enhanced employees’ understanding as reflected in the increase in post-test scores compared to pre-test scores. This efficiency improvement demonstrates that the implementation of PDCA and Kaizen 5S not only creates a cleaner and more organized work environment but also contributes to increased productivity and the company's competitiveness in the supply chain industry.